How Does Extended Reality Influence Consumer Decision Making? The Empirical Evidence from A Laboratory Experiment - Xi, Nannan; Bampouni, Elpida; Hamari, Juho (HICSS Conference Office University of Hawaii at Manoa, 2022)
Extended reality (XR) technologies such as virtual reality (VR) and augmented reality (AR) have been postulated to revolutionize many human endeavors commonly undertaken at a location such as work, education, shopping and so on. While this future scenario may become reality sooner or later in the future, it is an increasingly pertinent question how these technologies may affect our cognitive processing and related decision making. Especially in business and marketing, consumers’ decision making and choice plays the determining role in the business success. Therefore in this study we conduct a laboratory experiment in the shopping context for investigating the two main aspects of consumer decision making (quality and satisfaction) in four different extended reality conditions; physical reality, augmented reality, virtual reality and augmented virtuality (N = 160). The results show that XR technologies differentially influence consumer decision making. More specifically, AR had no significant effect on decision quality or satisfaction; while VR was positively associated with decision quality. In addition, there was no significant interaction effect between AR and VR on decision making.
Keywords: AR; VR; mr; shopping; decision making; fi=Tietotekniikka|en=Computer Science|